Exploratory Analysis of Literature on the Impact of Globalization on Finance - Loso Judijanto; Eva Yuniarti Utami; Rianti Setyawasih; Teddy Oswari (Westscience Press, 2023)
This exploratory analysis delves into the extensive body of literature examining the intricate relationship between globalization and finance in the contemporary era. As global economic forces continue to reshape financial landscapes worldwide, this study synthesizes insights from diverse disciplines, including economics, finance, sociology, and political science. The analysis uncovers the transformative power of globalization on financial structures, institutions, and market behaviors, revealing a nuanced interplay that extends beyond economic transactions. The literature review explores key themes such as the new dynamics of financial globalization, its effects on developing countries, and the role of technology, market structure, and policy responses. Additionally, it addresses the social and political consequences, emphasizing the need for a comprehensive understanding to inform regulatory frameworks and international cooperation. The method section details a systematic bibliometric analysis of Human Resource Management research in the context of globalization, providing key metrics, trends, and research opportunities. The results and discussion section identifies research trends, key articles, and potential terms for future exploration. Drawing implications from the analysis, the study advocates for adaptive strategies and a forward-thinking perspective to navigate the complexities of the interconnected global financial landscape.